(untitled) (Journal of Life and Earth Science, 2011)
There existed a large number of water bodies including rivers, Khals, lakes and low-lying areas in Dhaka, a thickly populated City and capital of the country. The water bodies played important roles on the natural environment of the City including its drainage system. Due to various natural and human induced reasons, the wetlands of the City have been shrinking with the passage of time. This study makes an attempt to identify the urban wetlands, emphasizing on the extent of their changes and subsequent impacts on physical environment of the area. For ascertaining the land-use pattern of the City, this study uses topographical map (Toposheet of 1960) and satellite images (Landsat TM, 1988 and ALOS VNIR, 2008). It also uses remote sensing and GIS based software (e.g. Arc GIS, Erdas Imagine) for this purpose. Statistical analysis has been carried out in order to process and analyze the data. The study observes that the wetlands of Dhaka city are changing very quickly. In 1960, the total area of water bodies and lowlands were 2952.02 and 13527.58 ha, respectively. Whereas in 1988, the total area of the same decreased to 2103.62 and 12717.73 ha, respectively. This deteriorated further, occupying an area of 1990.71 ha in 2008 which indicates that the lowlands continued to decrease. Thus the water bodies and lowlands decreased by 32.57% and 52.58%, respectively during 1960 and 2008. This changing trend of wetlands makes the drainage system of Dhaka City vulnerable, creating water logging problems and their consequences. Land filling and encroachment were recognized to be the main reasons for changing wetlands in the City. Key words: Wetlands; wetland changes; water logging; environment DOI: 10.3329/jles.v5i0.7348 J. Life Earth Sci., Vol. 5: 37-42, 2010